The Roma : a traveling history - Potter, Madeline (Harper, an imprint of HarperCollins Publishers, 2025)
A unique, deeply personal portrait of the nomadic Romani people and their on-going journey that sheds new light on their history, where they have traveled and settled, and what it means to be Romani today. --